A eficiência na decisão judicial de casos difíceis envolvendo empresas transnacionais no mercado digital - Leite, Geraldo Neves (2025)
This doctoral thesis proposes a study on the role of efficiency within the field of law. It aims to investigate the application of the principle of efficiency as a legal standard to be followed by judges when delivering rulings in complex cases involving transnational companies in the digital market. This issue is particularly relevant because technological advancements have significantly impacted the legal framework of society, and existing legislation often falls short of regulating all the behaviors arising from relationships between technology product and service providers and consumers, particularly in areas such as information sharing on social networks and e-commerce. These regulatory gaps sometimes lead to complex legal disputes, where judicial decisions may have economic and social repercussions that extend beyond the interests of the parties involved. In this context, employing the principle of efficiency as a basis for judicial decision-making appears reasonable, especially in cases concerning judicial review of public policies regulating the economic activities of transnational companies. Such decisions must not only meet criteria of legality and justice but also adhere to efficiency standards, given the need to analyze the practical consequences in the reasoning of the decision. Accordingly, this dissertation seeks to propose a model for applying the principle of efficiency in resolving complex cases involving business law issues, particularly those involving transnational technology companies operating in the digital market. The research includes a literature review of legal and economic theories as well as an analysis of landmark rulings by the Brazilian Federal Supreme Court (STF) and Superior Court of Justice (STJ), illustrating the application—or lack thereof—of the principle of efficiency as a decision-making criterion in cases involving internet service providers.